AB0815 CHANGES IN BODY COMPOSITION, BONE MINERAL DENSITY AND BONE REMODELING MARKERS DURING INTERLEUKIN 12/23 INHIBITION IN PSORIATIC ARTHRITIS. (2nd June 2020) - Paccou, J.; Bavière, W.; Chapurlat, R.; Sornay-Rendu, E.; Szulc, P.; Cortet, B.; Flipo, R. M.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by multiple comorbid conditions including cardiovascular comorbidities, diabetes, obesity and osteoporosis. Little is known about body composition in patients with PsA and no data are available regarding body composition changes under DMARDs. Objectives: We investigated the effects of ustekinumab (UST), a humanized anti-interleukin 12/23 antibody, on body composition, bone mineral density (BMD) and bone remodeling markers in patients treated for PsA. Methods: Thirty patients with active PsA treated with UST were included in a 6 months open follow-up study. Body mass index, DAS28-CRP, bone remodeling markers, serum levels of leptin, BMD and body composition (dual-energy X-ray absorptiometry) were measured at baseline and 6 months of treatment. At baseline, PsA patients were compared with 60 non-PsA controls matched for age, sex and body mass index. Results: Compared with controls, we observed lower total and appendicular lean mass (53.1 ±13.1 vs. 56.7 ±11.9 kg, p=0.013 and 21.6 ±6.3 vs. 23.4 ±5.0 kg, p=0.010 respectively) and greater fat mass in PsA (32.5 ±10.8 vs. 25.2 ±8.9 kg, p<0.001). Among PsA patients, 30% had a skeletal muscle mass index below the cut-off point for sarcopenia (Baumgartner's criteria: men 7.26 kg/m2, women 5.5 kg/m2) whereas no case was observed in the control group. After 6 months of treatment with UST, there was not a significant change of BMI, while there was a tendency for reaching the significant level for fat mass (+1.75 ±3.60 kg, p=0.054), and fat mass index (+0.59 ±1.25 kg/m 2, p=0.061). In contrast, a decrease in total lean mass was observed (-1.57 ±3.10 kg, p=0.046) without a significant change in appendicular lean mass and skeletal muscle mass index. No changes for bone remodeling markers, leptin and BMD were observed at 6 months. Conclusion: Patients with active PsA required biologic therapy had increased fat mass and decreased lean mass. Moreover, ustekinumab might worsen the decrease in lean mass with no significant change in fat mass. Disclosure of Interests: Julien Paccou Grant/research support from: Janssen, Speakers bureau: Abbvie, Amgen, Janssen, Lilly, MSD, Novartis, Pfizer, Sandoz, Sanofi, UCB, Wallis Bavière: None declared, Roland Chapurlat: None declared, Elisabeth Sornay-Rendu: None declared, Pawel Szulc: None declared, Bernard Cortet Consultant of: Aptissen, René-Marc Flipo Consultant of: Johnson and Johnson, MSD France, Novartis, Sanofi, Speakers bureau: Johnson and Johnson, MSD France, Novartis, Sanofi